Impoliteness Strategies and Social Dimensions in Enola Holmes 2 Movie: Socio-Pragmatics Study - Natalia, Rahma (JALL (Journal of Applied Linguistics and Literacy), 2024)
This research aims to identify the types of impoliteness strategies and to analyze the social dimensions in the Enola Holmes 2 movie. This research uses descriptive qualitative method as the purpose of making this research is to analyze the phenomenon of impoliteness. This research aims to identify the types of impoliteness strategies and analyze the social dimensions that influence the use of impoliteness. The theory used is Culpeper (2011) theory of impoliteness strategies and Holmes (2013) theory of the social dimension. The results of the research, there are 5 Bald on Record Impoliteness (23,8%), 11 Positive Impoliteness (52,4%), 2 Negative Impoliteness (9,5%), 3 Sarcasm or Mock Politeness (14,3%) and 0 Withhold Politeness (0%), and also found the social dimension that influence the use of impoliteness, there are 10 Social Distance Scale (47,6%), 8 Status Scale (38%), 0 Formality Scale (0%) and 3 Functional Scale (14,4%). The most common found types of impoliteness strategies found are Positive Impoliteness and most common found for the social dimensions that influence the use of impoliteness is Social Distance.